Movement and demography of Southern damselfly (Coenagrion mercuriale, Odonata) in a Mediterranean lotic ecosystem. Issue 2 (3rd March 2020) - La Porta, Gianandrea; Goretti, Enzo
Abstract : Home range, routine movement, and dispersal are key factors affecting the population distribution, thus playing a crucial role in spatial dynamics and gene flow. In this regard, detailed investigations on insects require the capture of the specimens and subsequent manipulation. The movement and the abundance of a population of the damselfly Coenagrion mercuriale were monitored using the mark-recapture method at a breeding site located in a Mediterranean watercourse in Central Italy. The study area was a transect of 250 m along a ditch, subdivided into five stretches varying from 40 to 70 m each. A total of 849 adults was captured and 210 specimens of them were recaptured on a 17-day survey (from mid-June to early July 2018), corresponding to an estimation of population size of 5, 600 specimens. Recapture and survival probabilities revealed no significant effect ensuing from handling and marking with different colours. Specimens of different stretches showed different sedentary rate. The recaptured individuals had a low vagility, with a high proportion of individuals which are incline to philopatry.